AA.VV., Monografías del exilio español 12: Expatriados, Madrid, Asociación “Memoria Viva”, 2016, 621 págs., ISBN: 978-84-608-7676-2 - Rodríguez Hernández, Juan Pedro (2018)
Fil: Rodríguez Hernández, Juan Pedro. Investigador Independiente; Argentina